Genetic Diversity For Submergence Tolerance In Rice (Oryza Sativa L.) Utilizing Ssr Markers (Applied Biological Research, 2019)
The present study was aimed to analyze molecular diversity of submergence  tolerant genotypes of rice. Thirty four SSR primers were used to generate allelic variants (4 alleles in RM 23843 and 27 in RM 23662). Altogether 410 allelic variants were detected at 42 SSR loci with a mean of 9.76 alleles per  locus. Analysis of divergence pattern based on SSR markers allowed  differentiation and classification of rice varieties into 8 clusters. A large  range of similarity coefficient revealed by SSR markers provided greater  confidence for the assessment ofgenetic divergence and interrelationship  among the submergence tolerant rice genotypes. A perusal of similarity  coefficients reflected a very high degree of similarity between rice genotypes  ‘Anh Hsung Seln’ (C 11) and ‘Hsung Teing’, whereas ‘FR 13A’ and ‘Swarna  Sub-1’ were more diverse for breeding programme to generate more  recombinants. Use of SSR markers appeared more efficient in achieving  unique and unambiguous characterization and differentiation of varieties  used in the present study. The SSR analysis also revealed unique or variety specific allele which could be useful as DNA fingerprints in the identification  and preservation of different genotype and to develop highly submergence tolerance varieties.
Keywords: Allele; divergence; loci; rice; submergence